If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8u = -7u Solving 5 + -8u = -7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '7u' to each side of the equation. 5 + -8u + 7u = -7u + 7u Combine like terms: -8u + 7u = -1u 5 + -1u = -7u + 7u Combine like terms: -7u + 7u = 0 5 + -1u = 0 Add '-5' to each side of the equation. 5 + -5 + -1u = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1u = 0 + -5 -1u = 0 + -5 Combine like terms: 0 + -5 = -5 -1u = -5 Divide each side by '-1'. u = 5 Simplifying u = 5
| 8t-9=10t+9 | | 5x=31+2x+11 | | 6x+10-3x=8+2x-5 | | -r^2+8r=0 | | 2cosx-5=0 | | 3y+9=2y-4 | | 6+10-3x=8+2x-5 | | Y=5z-8 | | 15x+3(4x-6)=3x+9-9x | | (2x-4)+X=28 | | 7x=5+3x+19 | | 8h=10h+6 | | x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 | | 2x-4+x=28 | | 24=-8u+5(u+6) | | 2x^2+2y^2-2xy-2x+4y+5=0 | | 3x^2+27x-6.5=0 | | 8(x-3)+9=5x+3(-4+x) | | 15-27=2(21) | | 5w=6w+7 | | .65x+18.50=.75x+18.50 | | 5s+8t=70 | | 6x^3-x^2-27x-20=0 | | (-81)/(+9)= |